Biological Properties and Therapeutic Applications of Propolis - Sforcin, José M. [UNESP] (Wiley, 2016)
Propolis is a resinous material collected by bees from bud and exudates of the plants, mixed with bee enzymes, pollen and wax. In this review, the biological properties of propolis and some therapeutic applications are discussed. The same biological activities have been investigated until today, using samples from different geographic regions. Thus, the study of the biological properties of a given sample should always be associated with its chemical composition and botanical source, representing a particular sample of a given geographic area, exploring its biological potential and the role of its constituents. Efforts have been carried out to explain propolis' mechanisms of action in vivo and in vitro, but the majority of propolis' targets and actions are still unclear. The number of formulations containing propolis and patents have increased, although propolis extracts have been used deliberately with different recommendations, not always mentioning the chemical composition, vegetal source and the methods of extraction. Clinical studies will help to obtain criterious recommendations in view of the expected outcomes. Further investigation should explore the effects of common compounds found in the samples from all over the world in an attempt to standardize the research on propolis and to obtain new drugs.
Keywords: biological properties; propolis; therapeutical applications